2005
DOI: 10.1186/1471-230x-5-37
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of leptin against ischemia-reperfusion injury in the rat small intestine

Abstract: Background: The small intestine is extremely sensitive to ischemia-reperfusion (I/R) injury and a range of microcirculatory disturbances which contribute to tissue damage. Previous studies have shown that leptin plays an important physiological role in the microvasculature. The aim of this study was to evaluate the protective effects of leptin in I/R -induced mucosal injury in the small intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
0
27
1
5
Order By: Relevance
“…The protective effect of leptin in intestinal IR injury has recently been demonstrated [24,25]. Hacioglu et al performed intestinal IR injury in adult Wistar rats weighting 200-250 g, but we used 140±14.5 g rats, aged 8 weeks in our study [24]. In contrast to our study, they did not report any significant difference in intestinal injury to the ileum between IR + leptin group and IR group.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The protective effect of leptin in intestinal IR injury has recently been demonstrated [24,25]. Hacioglu et al performed intestinal IR injury in adult Wistar rats weighting 200-250 g, but we used 140±14.5 g rats, aged 8 weeks in our study [24]. In contrast to our study, they did not report any significant difference in intestinal injury to the ileum between IR + leptin group and IR group.…”
Section: Discussioncontrasting
confidence: 54%
“…Kimura et al have suggested that arterial relaxation by leptin is mediated by NO released from the endothelium [23]. The protective effect of leptin in intestinal IR injury has recently been demonstrated [24,25]. Hacioglu et al performed intestinal IR injury in adult Wistar rats weighting 200-250 g, but we used 140±14.5 g rats, aged 8 weeks in our study [24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Leptin has been reported to act as a mitogenic agent and stimulates the growth of several obesity-associated advanced human cancers, including breast cancer, 25 colon cancer, 26 endometrial cancer 27 and renal cancer. 28 The use of leptin in these patients to prevent chemotherapy-induced mucositis should be probably avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, leptin induces aromatase expression in adipose tissue followed by the elevation of estrogen (30); estrogen and its receptors are involved in learning, so the effect of leptin on memory may in part be due to its effects on estrogen (31) through the increased amounts of nitric oxide and acetylcholine in the brain (32). Leptin also triggers the release of NO in some tissues including the hypothalamus, anterior pituitary gland (33) and mesenteric vasculature (34). Since leptin receptors are also present in the hippocampus, it is possible that leptin, through NO, plays a helpful role in memory in the hippocampus.…”
Section: Figmentioning
confidence: 99%